2020
DOI: 10.1155/2020/4690974
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Management and Analytics in Scientific Programming: A Deep Learning-Based Method for Aspect Category Classification of Question-Answering-Style Reviews

Abstract: Online product reviews are exploring on e-commerce platforms, and mining aspect-level product information contained in those reviews has great economic benefit. The aspect category classification task is a basic task for aspect-level sentiment analysis which has become a hot research topic in the natural language processing (NLP) field during the last decades. In various e-commerce platforms, there emerge various user-generated question-answering (QA) reviews which generally contain much aspect-related informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The collection process of the crawler system may vary according to the specific application scenarios and functional requirements, but in general, it can be summarized as the following steps. Figure 2 shows the corresponding collection process [13].…”
Section: Methodsmentioning
confidence: 99%
“…The collection process of the crawler system may vary according to the specific application scenarios and functional requirements, but in general, it can be summarized as the following steps. Figure 2 shows the corresponding collection process [13].…”
Section: Methodsmentioning
confidence: 99%
“…Another thrilling revelation is that most studies [70,77,79,84,94,97,106,108,[116][117][118][119][120][121] used Deep Neural Networks (DNN), such as LSTM and Convolutional Neural Network (CNN), as shown in Fig. 6.…”
Section: Big Data Platforms Tool In Bdamentioning
confidence: 99%
“…We observed that several studies [70,83,85,87,88,92,95,97,104,108,117,119,122,124,125] combined two or more metrics to evaluate their models and framework.…”
Section: Evaluation Metrics Used In Bdamentioning
confidence: 99%
See 1 more Smart Citation
“…(Our research differs from the work they built on conventional reviews, our proposed model is based on Q&A-style reviews and we leverage conditional random fields to further improve ATE's performance.) More recently, Wu et al [33] proposed a 4-dimension textual representation model on Q&A style reviews for ACC task.…”
Section: Aspect Category Classificationmentioning
confidence: 99%